Use of pilotless aircraft in modern warfare. Assessing their lawfulness under International Humanitarian Law - Ramírez García de León, Xavier J. (2021)
Despite the advanced technology required for their operation, drones represent another stage in the human tradition of developing means for waging war remotely. In this sense, they are no different from other advancements and are subject to the same international standards and must comply with the same principles as other weapon-platforms. This article focuses on providing an answer on the legality of the use of drones in relation to International Humanitarian Law. To do so, it briefly addresses the issue of the use of drones in the most common scenario, attacks against non-state armed groups in foreign territory, and then concentrates on the compliance with the principles of international humanitarian law, in order to conclude that their characteristics not only allow them to comply with but also may even be regarded as an enhancement in the constant pursuit of enforcing International Humanitarian Law.